Tindak Tutur Expresif dalam Kolom Komentar Akun Instagram Gibran Rakabuming Raka - Fitriliani, Mella; Asnawi, Asnawi (UIR Press, 2025)
Expressive speech acts are an integral part of online communication, allowing users to express their feelings, attitudes, and emotions directly. This study aims to analyze expressive speech acts found in the comments column of Gibran Rakabuming Raka's Instagram account. Expressive speech acts are an integral part of online communication, allowing users to express their feelings, attitudes, and emotions directly. This study uses a qualitative approach with a descriptive method to systematically describe, explain, describe, and analyze expressive speech acts based on data collected on May 6, 2025. The data consists of netizens' comments containing expressive speech acts, such as thanking, congratulating, praising, blaming, and others. Data collection techniques use documentation (screenshots), listening techniques to observe comments, and recording by classifying data according to the type of expressive speech act based on Searle's theory (1979). The analysis technique used is content analysis. The results of the study show that the types of expressive speech acts found include thanking, congratulating, praising, blaming, and apologizing, with the dominant form being praise for Gibran. This research reveals that social media is a crucial space for public expression of attitudes toward political figures.